2013
DOI: 10.1007/s11605-013-2330-2
|View full text |Cite
|
Sign up to set email alerts
|

Delaying Cholecystectomy for Complicated Gallstone Disease in Pregnancy is Associated with Recurrent Postpartum Symptoms

Abstract: The majority of patients with CGD who do not undergo antepartum cholecystectomy have recurrent postpartum symptoms often within 3 months postpartum. When appropriate, physicians should advocate for antepartum or early postpartum cholecystectomy to minimize symptom recurrence and unplanned hospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 16 publications
2
18
0
4
Order By: Relevance
“…Symptomatic cholelithiasis can also lead to complicated biliary disease, including cholecystitis, pancreatitis, choledocholithiasis, and cholangitis. We have previously shown that delaying cholecystectomy for complicated gallstone disease results in early postpartum gallstonerelated symptoms and repeat hospitalizations [ 16 ]. However, there is little data regarding the outcomes for patients with uncomplicated symptomatic cholelithiasis (SC) in pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic cholelithiasis can also lead to complicated biliary disease, including cholecystitis, pancreatitis, choledocholithiasis, and cholangitis. We have previously shown that delaying cholecystectomy for complicated gallstone disease results in early postpartum gallstonerelated symptoms and repeat hospitalizations [ 16 ]. However, there is little data regarding the outcomes for patients with uncomplicated symptomatic cholelithiasis (SC) in pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Patients treated with nonoperative management are at a significant risk for recurrent symptoms; during the third trimester, if surgery is not performed, antepartum ERCP and endoscopic sphincterotomy appear to be protective with a decrease of symptom recurrence, but early postpartum cholecystectomy is strongly recommended [88][89][90]. In case of severe AP, most often due to hypertriglyceridemia, and life-threatening for the mother and fetus, a pregnancy interruption is mandatory, as soon as possible, either by abortion or by delivery if possible [91].…”
Section: Acute Pancreatitis and Pregnancymentioning
confidence: 99%
“…There are no extensive prospective studies addressing perinatal outcomes or clinical trials on this topic. However, several small studies have shown laparoscopic cholecystectomy during pregnancy to be generally safe for mother and foetus [75].…”
Section: Acute Cholecystitis In Pregnancymentioning
confidence: 99%